Foreign women - women in foreign lands studies on foreignness and gender in the Hebrew Bible and the Ancient Near East in the first millennium BCE - Berlejung, Angelika 1961-; Grohmann, Marianne 1969- (Tübingen Mohr Siebeck, 2019)
Cover -- Titel -- Preface -- Table of Contents -- Abbreviations -- LARS ALLOLIO-NÄCKE: How to Become an Alien (Woman)? -- SARA JAPHET: Marriage with Foreign Women: Yes or No? -- ANGELIKA BERLEJUNG: Solomon's Soulmate: The Queen of Sheba as a Foreign Woman -- NILI WAZANA: Rahab, the Unlikely Foreign Woman of Jericho (Joshua 2) -- MARIANNE GROHMANN: The Philistine Woman from Timnah in Judges 14:1-15:8 -- DANIEL BODI: When YHWH's Wife, Jerusalem, Became a Strange Woman -- STEFAN FISCHER: Foreign Women in the Book of Proverbs -- JAN DIETRICH: The Image of the Foreign Woman in Prov 1-9 -- HANS-PETER MATHYS: Phoenicians and Money Bags: Observations on Prov 7 -- HANS-PETER MATHYS: The Valiant Housewife of Prov 31:10-31: A Phoenician Businesswoman -- JUTTA HAUSMANN: Pharaoh's Daughter and Ruth: Cornerstones in the History of Israel -- AGNETHE SIQUANS: A Moabite Woman as the 'Right Son': Ruth as Naomi's and Boaz's Daughter -- KRISTIN JOACHIMSEN: Esther in Shushan -- FRANZISKA NAETHER: Ancient Expats? Wise Women and Witches in Egyptian Literary Sources -- ANGELIKA BERLEJUNG: Forever Foreign? Marriage Rules in Urban Babylonia and their Impact on the Exiles and Returnees -- Indexes -- Index of Sources -- 1. Old Testament -- 2. New Testament -- 3. Apocrypha and Pseudepigrapha -- 4. Rabbinic Literature -- 5. Egypt -- 6. Ancient Near East -- 7. Classical Sources -- Index of Ancient Names -- 1. Persons, Mythological Figures and Deities -- 2. Geographical Names -- Index of Subjects.
The volume presents a collection of papers read during three workshops held in Leipzig (2016), Jerusalem (2017), and Vienna (2018). International scholars from different disciplines and methodological approaches explored gender-specific constructions of foreignness/strangeness in the Old Testament, Egypt, and Mesopotamia from their particular perspectives. They showed that when combined, strangeness/foreignness and gender can take on very different forms. Various processes of the "othering" of women are of importance, which differ from the "othering" of men. The contributions investigate specific questions, individual female figures and individual phenomena as model cases. The basic question was when, where, how and for what purpose the categories of foreignness and gender were connected and activated in literary tradition. The collection is a preliminary and basic work for further study of gender-specific concepts of foreignness/strangeness in the ancient Mediterranean cultures of the first millennium BCE. --
The volume presents a collection of papers read during three workshops held in Leipzig (2016), Jerusalem (2017), and Vienna (2018)
Keywords: Women in the Bible; Noncitizens -- Biblical teaching; Electronic books; Femmes dans la Bible; Women in the Bible; Women in the Bible; Aliens - Biblical teaching; proceedings (reports); Conference papers and proceedings; Conference papers and proceedings; Actes de congrès; Konferenzschrift -- 2016 -- Leipzig; Konferenzschrift -- 2017 -- Jerusalem; Konferenzschrift -- 2018 -- Wien; Aufsatzsammlung